Production Functions and British Coal Mining - Leser, C. E. V. (Econometrica, 1955)
The method used here represents an attempt to eliminate the influence of unspecified factors on the dependent variate in multiple regression analysis. It is applied in constructing a production function for British coal mining over the period 1943-53 and in estimating the elasticities of output with regard to labour and to horsepower, the latter indicating mechanisation. The statistical and economic significance of the results is examined.